Exogenous Abscisic Acid Regulates Distribution of 13C and 15N and Anthocyanin Synthesis in ‘Red Fuji’ Apple Fruit Under High Nitrogen Supply - Wang, Fen; Sha, Jianchuan; Chen, Qian; Xu, Xinxiang; Zhu, Zhanling; Ge, Shunfeng; Jiang, Yuanmao (Frontiers in Plant Science, 2020)
In order to improve the problem of poor coloring caused by high fruit nitrogen in apple production, we studied the effects of different concentrations of abscisic acid (ABA: 0, 50, 100, 150 mg/L) and fluridone (ABA biosynthesis inhibitor) on the fruit of ‘Red Fuji’ apple (Malus Domestica Borkh.) in the late stage of apple development (135 days after blooming) in 2017 and 2018. The effects of these treatments on the distribution of 13C and 15N and anthocyanin synthesis in fruit were studied. The results showed that the expression levels of ABA synthesis and receptor genes in the peel and flesh were up-regulated by exogenous ABA treatment. An appropriate concentration of ABA significantly increased the expression of anthocyanin synthesis genes and transcription factors and increased the content of anthocyanin in the peel. The results of 13C and 15N double isotope labeling showed that exogenous ABA coordinated the carbon-nitrogen nutrient of apple fruit in the late stage of the development, reduced the accumulation of fruit nitrogen, increased the accumulation of fruit carbon and sugar, provided a substrate for anthocyanin synthesis, or promoted anthocyanin synthesis through the sugar signal regulation mechanism. Comprehensive analysis showed that the application of 100 mg/L ABA effectively improved the problem of poor coloring caused by high fruit nitrogen in the late stage of apple development and is beneficial to the accumulation of carbon in fruit and the formation of color.